(untitled) (Journal of Pharma Insights and Research, 2026)
Postural instability and gait disturbances are clinical challenges in the management of Parkinson’s disease, frequently resulting in a loss of autonomy and an elevated incidence of falls. Conventional rehabilitation often fails to address the complex sensory deficits inherent in the disease. This research work evaluates the comparative impact of two distinct neurorehabilitation paradigms: Virtual Reality-based training, which utilizes enriched multisensory feedback, and Blindfolded Balance Training, which emphasizes proprioceptive and vestibular reliance through visual occlusion. 30 participants with idiopathic Parkinson’s disease (Hoehn and Yahr stages II–III) were randomized to receive either virtual reality interventions or blindfolded exercises, both supplemented by conventional physiotherapy, over a four-week period. Assessments conducted via the Berg Balance Scale and the Timed Up and Go test reveal significant improvements in both cohorts post-intervention. Statistical analysis demonstrates that while both modalities are effective, virtual reality-based training provides superior gains in both static and dynamic balance parameters. The interactive and task-specific nature of the virtual environment appears to facilitate more robust motor learning and neurological adaptation compared to isolated sensory reweighting. These results indicate that incorporating technologically driven feedback mechanisms into physical therapy protocols enhances functional outcomes. While immersive technology offers more pronounced benefits, blindfolded training remains a viable, resource-efficient strategy for promoting sensory-motor integration. Utilization of these diverse sensory training methods could offer a more holistic approach to neurorehabilitation, targeting the multifaceted motor impairments characteristic of progressive parkinsonism